Temporal Envelope of Time-Compressed Speech Represented in the Human Auditory Cortex - Nourski, Kirill V. (Society for Neuroscience, 2009)
Speech comprehension relies on temporal cues contained in the speech envelope, and the auditory cortex has been implicated as playing a critical role in encoding this temporal information. We investigated auditory cortical responses to speech stimuli in subjects undergoing invasive electrophysiological monitoring for pharmacologically refractory epilepsy. Recordings were made from multicontact electrodes implanted in Heschl's gyrus (HG). Speech sentences, time compressed from 0.75 to 0.20 of natural speaking rate, elicited average evoked potentials (AEPs) and increases in event-related band power (ERBP) of cortical high-frequency (70–250 Hz) activity. Cortex of posteromedial HG, the presumed core of human auditory cortex, represented the envelope of speech stimuli in the AEP and ERBP. Envelope following in ERBP, but not in AEP, was evident in both language-dominant and -nondominant hemispheres for relatively high degrees of compression where speech was not comprehensible. Compared to posteromedial HG, responses from anterolateral HG—an auditory belt field—exhibited longer latencies, lower amplitudes, and little or no time locking to the speech envelope. The ability of the core auditory cortex to follow the temporal speech envelope over a wide range of speaking rates leads us to conclude that such capacity in itself is not a limiting factor for speech comprehension.